Petrographic and Geotechnical Characterization of the Magmatic Formations from Hadjer El-Hamis and Dandi (Hadjer-Lamis Province, Chad) for Their Use in Civil Engineering - HAMID ZAGALO, AL-HADJ (European Journal of Applied Sciences, 2022)
This paper deals with the magmatic rocks from Hadjer El-hamis and Dandi located in the Hadjer-Lamis Province (Chad). Indeed, Chad is actually engaged in several construction project and consequently needs a large quantity of good quality construction materials. The present study is in straight line with this logic and aims to determine the petrographic and geotechnical characteristics of the Hadjer Lamis rocks in order to define their use in civil engineering. In this area, rocks outcrop in the form of mounds displaying hexagonal, pentagonal and tetragonal prisms in Hadjer El-hamis, and as fractured blocks in Dandi. Petrographic analyses show that rocks from Hadjer El-hamis are rhyolite displaying porphyritic to locally glassy microlitic texture with mineralogical quatz, alkaline feldspar, pyroxene, biotite and opaque minerals. Rocks from Dandi granites (microgranite, porphyritic microgranite and granite) with massive structure and fine grained (microgranite), fine grained porphyritic micrograined and gritty texture composed of quartz, orthose, plagioclase, pyroxene, biotite and opaque minerals of variable proportions from one rock to another. The geotechnical analyses carried out on the crushed masses of the sites of Hadjer El-hamis and Dandi concerned their physical and mechanical characteristics. Their physical characteristics show that their average specific density values are 2.40g/cm3 and 2.60g/cm3 and bulk density are 1.41g/cm 3 and 1.38 g/cm 3 respectively for Hadjer El-hamis and Dandi samples. The average values of flattening coefficients are respectively 12.19% and 10.6% for Hadjer El-hamis and Dandi areas. The mechanical characteristics of the studied materials on the basis of average values show that building materials from Hadjer El-hamis resist better to wear than those from Dandi, This difference in mechanical properties is certainly due to the petrographic nature characterized respectively by volcanic rocks in Hadjer El-hamis and plutonic in Dandi. Regarding resistance to impact, the geotechnical material from these two areas show very close average values of Los-Angeles coefficient and dynamic fragmentation coefficient recommended for civil engineering works. It appears from this research work that the studied materials are recommended for civil engineering work except for the sample E6 which presents too high Micro-Deval and Los-Angeles coefficients thus requiring a preliminary treatment before use.